2019
DOI: 10.3892/ol.2019.11035
|View full text |Cite
|
Sign up to set email alerts
|

An extra chromosome 9 derived from either a normal chromosome�9 or a derivative chromosome 9 in a patient with acute myeloid leukemia positive for t(9;11)(p21.3;q23.3): A case report

Abstract: Translocation (9;11)(p21.3;q23.3) is one of the most common lysine methyltransferase 2A (KMT2A)-rearrangements in de novo and therapy-related acute myeloid leukemia (AML). Numerous in vitro and in vivo studies have demonstrated that the KMT2A/MLLT3 super elongation complex subunit (MLLT3) fusion gene on the derivative chromosome 11 serves a crucial role in leukemogenesis. Trisomy 9 as a secondary chromosome change in patients with t(9;11) is relatively rare. The present study reported a unique case of AML with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Array CGH analysis was performed on genomic DNA isolated from an uncultured bone marrow specimen collected during the initial visit using a commercial DNA extraction kit (Puregene Blood Kit; Qiagen, Valencia, CA) to reveal the precise breakpoints of the microdeletion, according to the manufacturer's instructions. [ 13 ] A 2.016-Mb deletion from 3q25.31 to 3q25.32 (position 156,296,873-158,312,638 on hg19) was identified in this patient (Fig. 4 A).…”
Section: Case Presentationmentioning
confidence: 77%
“…Array CGH analysis was performed on genomic DNA isolated from an uncultured bone marrow specimen collected during the initial visit using a commercial DNA extraction kit (Puregene Blood Kit; Qiagen, Valencia, CA) to reveal the precise breakpoints of the microdeletion, according to the manufacturer's instructions. [ 13 ] A 2.016-Mb deletion from 3q25.31 to 3q25.32 (position 156,296,873-158,312,638 on hg19) was identified in this patient (Fig. 4 A).…”
Section: Case Presentationmentioning
confidence: 77%
“…Isolated trisomy 9 is considered a low-to-intermediate risk factor, but in concurrence with other cytogenetic abnormalities, it may result in the rapid progression of disease with consequent poor prognosis. 6 7 10 Delaunay et al showed that the presence of other additional chromosome structure or number abnormalities or persistence of normal metaphases had no significant impact on CR rate. 11 12 13 Its role in prognostic stratification of AML is not well established due to the rarity of its occurrence.…”
Section: Discussionmentioning
confidence: 99%